2021
DOI: 10.3389/fsurg.2021.726067
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Magnetic Resonance Imaging Histograms in the Preoperative Differential Diagnosis of Endometrial Stromal Sarcoma and Degenerative Hysteromyoma

Abstract: Objective: The present study aimed to explore the application value of magnetic resonance imaging (MRI) histograms with multiple sequences in the preoperative differential diagnosis of endometrial stromal sarcoma (ESS) and degenerative hysteromyoma (DH).Methods: The clinical and preoperative MRI data of 20 patients with pathologically confirmed ESS and 24 patients with pathologically confirmed DH were retrospectively analyzed, forming the two study groups. Mazda software was used to select the MRI layer with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…Our results for sensitivity and diagnostic accuracy are slightly higher than those of previous study. Zhang et al ( 26 ) found that the sensitivity and specificity of MRCP in the differential diagnosis of gallbladder lesions were 92% and 93%, respectively, which are close to the findings of this study and confirm the high clinical method efficiency of MRCP. This study showed that the detection rate of lesions <0.5 cm in diameter by MRCP (32.05%) was higher than that by MSCT (14.00%; P<0.05).…”
Section: Discussionsupporting
confidence: 90%
“…Our results for sensitivity and diagnostic accuracy are slightly higher than those of previous study. Zhang et al ( 26 ) found that the sensitivity and specificity of MRCP in the differential diagnosis of gallbladder lesions were 92% and 93%, respectively, which are close to the findings of this study and confirm the high clinical method efficiency of MRCP. This study showed that the detection rate of lesions <0.5 cm in diameter by MRCP (32.05%) was higher than that by MSCT (14.00%; P<0.05).…”
Section: Discussionsupporting
confidence: 90%